2013
DOI: 10.1113/expphysiol.2013.073874
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle capillary function: contemporary observations and novel hypotheses

Abstract: The capillary bed constitutes a vast surface facilitating exchange of O2, substrates and metabolites between blood and organs. In contracting skeletal muscle capillary blood flow and O2 diffusing capacity as well as O2 flux may increase two orders of magnitude above resting. Chronic diseases such as heart failure, diabetes and also sepsis impair these processes leading to compromised energetic, metabolic and ultimately contractile function. Among researchers seeking to understand blood-myocyte exchange in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
143
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(154 citation statements)
references
References 100 publications
9
143
2
Order By: Relevance
“…When the microcirculation is visualized using imaging and video techniques in a contracting skeletal muscle, there is marked dilation in all elements of the arteriolar tree, with the most pronounced dilation seen in the smallest arterioles (487,488). Recent evidence also suggests that in many preparations up to ϳ80% of capillaries are perfused at rest, challenging the older idea that capillary recruitment is a major phenomenon contributing to exercise hyperemia and gas exchange in contracting skeletal muscles (363).…”
Section: A Site Of the Vasodilationmentioning
confidence: 91%
“…When the microcirculation is visualized using imaging and video techniques in a contracting skeletal muscle, there is marked dilation in all elements of the arteriolar tree, with the most pronounced dilation seen in the smallest arterioles (487,488). Recent evidence also suggests that in many preparations up to ϳ80% of capillaries are perfused at rest, challenging the older idea that capillary recruitment is a major phenomenon contributing to exercise hyperemia and gas exchange in contracting skeletal muscles (363).…”
Section: A Site Of the Vasodilationmentioning
confidence: 91%
“…The efforts of many, including Matheau-Costello and colleagues (37,38) and Poole and colleagues (44,45), have established that in the vascular system the capillary surface area is correlated directly with the mitochondrial content and maximal demand for oxidative phosphorylation. Almost everything else related to the role of oxygen is controversial, with widely differing opinions expressed in the literature as to the oxygen dependence of oxidative phosphorylation as well as the oxygen pressure in the cellular and mitochondrial environments.…”
Section: E508 Programming and Regulation Of Metabolic Homeostasismentioning
confidence: 99%
“…Contrary to the pioneering model proposed by August Krogh (177,178), compelling contemporary experimental and theoretical evidence has shown that intramyocyte O 2 diffusion distances do not limit mitochondrial O 2 delivery in healthy muscles (therefore negating the notion of intracellular anoxic loci; Refs. 131,246,247). Thus, given that the major resistance to skeletal muscle O 2 diffusion from the RBC to the mitochondria resides at the capillary-myocyte interface (i.e., the so-called "carrier-free region") and the very low and uniform intramyocyte PO 2 values (92,103,256), it may be tempting to speculate that potential alterations in fiber cross-sectional area and/or mitochondrial distribution might not impact D mO 2 significantly in diseased or exercise-trained states.…”
Section: Exercising Blood-muscle O 2 Flux In Health and Chf: Mechanismentioning
confidence: 99%